What women Want or Need? Writing the female Self. Case Study: Spivakian Reading to Toni Morrison’s Beloved - Ouakouak, Zohra; Bekkari, Nour El Houda (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة الحالية إلى تحليل أعمال توني موريسون "الحبيبة" ، وتمييز مختلف علامات التبعية الواردة في الرواية من خلال استخدام مبادئ نظرية سبيفاكيان لكتابة الذات الأنثوية. تمثل الدراسة تحليلاً نوعياً اعتمد منهجاً تحليلياً لفحص الرواية واستخراج علامات وأمثلة على التبعية وبناء الذات الأنثوية. يهدف العمل إلى كشف الحقائق والقصص المأساوية للأقليات وإيصال أصواتهم وألمهم إلى العالم. تكشف الدراسة أن مظاهر الصدفية والجوهرية حية في الرواية من خلال تجربة الشخصيات النسائية في المجموعة. ومع ذلك ، خلقت تجاربهم إحساسًا بالمقاومة رفضت من خلاله نفس الشخصيات النساء واقعهن وكتبن مصائرهن. The current study aims to analyze the work of Toni Morrison “Beloved”, and mark the various signs of subalternity contained in the novel through the use of the principles of the Spivakian theory of writing the female self. The study represents a qualitative analysis which adopted an analytical method to examine the novel and extract signs and examples of subalternity and constructing the female self. The work aims to unravel the tragic realities and stories of the minorities and deliver their voices and pain to the world. The study reveals that the aspects of sablternity and essentialism are vivid in the novel through the experience of the women characters in the corpus. Yet, their experiences created a sense of resistance through which the same women characters refused their reality and wrote their own destinies.
Master’s Degree in Literature and Civilization
Keywords: الحبيبة ، نظرية سبيفاكيان ، التبعية. توني موريسون ، كتابة الذات إنجليزية; Beloved, Spivakian theory, Subalternity. Toni Morrison, Writing the Self